Analisis Komponen Fisik Terhadap Kemampuan Shooting Pada Permainan Sepakbola Siswa MAN 2 Kota Makassar - Herman, Herman; Karim, Achmad (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This research aimed to find out: (1) the correlation between leg eye coordinationAnd shooting ability in soccer games; (2) the correlation between leg muscleÂ  strength and shooting ability in soccer games; (3) the correlation between legÂ  power explosion and shooting ability in soccer games; (4)Â  the correlation betweenleg eye, leg muscle strength and leg power explosion on shooting ability in soccerfor the students of physical education department of MAN 2 Kota Makassar.Â  Thetotal sample of the research was 30 students using simple random sampling technique. Technique of data analysis was descriptive correlation, regressiveÂ  analysis on the significant level was Î±= 0,05 using SPSS version 21. The result of the research indicated that:Â  (1) There is a significant correlation between leg eyeÂ  coordination and shooting ability in soccer games, with a value of r= 0.751 (Ï < = 0.05); (2) There is a significant correlation between leg muscle strength andÂ  shooting ability in soccer games, with a value of r =0.657 (Ï < = 0.05); (3) There is a significant correlation between leg power explosion and shooting ability in soccer games, with a value of r= 0.620(Ï < = 0.05); (4) There is a significant correlation simultneously between leg eye, leg muscle strength and legÂ  powerÂ  explosionÂ  onÂ  shootingÂ  abilityÂ  insoccerÂ  forÂ  theÂ  studentsÂ  ofÂ  physical education department of MAN 2 Kota Makassar, with the determinant coefficient (R2) = 0.679 or 67.9 %